ANALISIS LIRIK LAGU PADA SEVENTEEN DAN SMILE FLOWER: KAJIAN SEMIOTIKA RIFATERRE - Ni Nyoman Anita Dewi Ardiningsih; I Wayan Wahyu Cipta Widiastika (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
The analysis of the song prioritizes the analysis of its meaning. In song lyrics, there are many figurative meanings that if not studied more deeply will lead to misinterpretation, so that the meaning to be conveyed cannot be digested by listeners and fans of the song. Especially foreign-language songs, which must be translated first, then extra closely examine the message contained so that no misinterpretation occurs. An example of a foreign language song is Japanese. Seventeen, is a K-pop idol who has a successful career in Japan with many achievements. One of their albums titled